Service improvement system to enhance the safety of patients admitted on long-term warfarin. Issue 1 (19th March 2014) - Warcel, Dana; Johnson, Daniel; Shah, Neeraj; shreeve, Norman
Abstract: It is common for hospital inpatients on warfarin to suffer from fluctuations in their INR (international normalised ratio). Raised INRs are potentially very dangerous and may result in acute life-threatening haemorrhages. Conversely, low INRs may increase the risk for the development of venous thromboembolism. Having observed many deranged INRs among hospital inpatients, we decided to focus our project on identifying the contributing factors to deranged INRs and ways to address this problem. We analysed the warfarin prescriptions on all drug charts and surveyed the junior doctor staff. Our results revealed poor knowledge and confidence levels on warfarin prescribing among junior doctor staff. This is likely to be reflected in the poor completion rate of warfarin prescriptions. We instituted practical changes to resolve the issue: most importantly, a change to the warfarin administration time from 6 pm to 2 pm, supported by a poster campaign to increase awareness of the problem. The objective of these changes was to reduce prescribing errors by reducing warfarin prescriptions out-of-hours, by the on-call doctors. We repeated the audit cycle twice. Although our interventions were successfully introduced as shown in our second audit cycle, the changes that were implemented were not sustained as shown in the third audit cycle. We identified a need for annual intervention to educate new junior doctor staff to ensure that the positive outcomes achieved are maintained in the long term.